EPIDEMIOLOGICAL AND DEMOGRAPHIC ISSUES OF THE PREVALENCE OF ATOPIC DERMATITIS - Irsaliyeva, F.Kh.; Razikova, G.R. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Over the past decade, significant progress has been made in understanding the pathogenetic mechanisms of the development and course of atopic dermatitis. To a certain extent, this knowledge was obtained thanks to a breakthrough in large-scale research on the epidemiology and treatment results of atopic dermatitis, as well as genetic studies, immunological and in-depth molecular biochemical studies for this disease.